Characters in Ma’mun Affany’s Novel 29 Juz Harga Wanita - Sembiring, A A (KnE Social Sciences, 2018)
This study is concerned about the analysis of a novel which focuses on the characters of the protagonist named Toni in the novel 29 Juz Harga Wanita written by Ma’mun Affany in 2010. The novel is about a hard man but yearning for a women’s tenderness. The man has been silenced by his father for twenty years. He also loves a graceful girl who is able to change Toni’s mindset so that Toni turns into a better man in his life. The objectives of this study are to reveal the protagonist’s characters and to analyse how the protagonist’s characters reflected in the novel. The theory of characters is adopted from Lickona (2004). The protagonist’s characters depicted in the novel cover four aspects: fortitude, self control, and hard work. The study was conducted by using descriptive qualitative method proposed by Moleong (2013). The findings of this study show that the protagonist has presented good characters in the novel which are worth adopting to put into practice in real life. Such good characters as fortitude, self control, and hard work are evidently depicted in the novel. The conclusion shows that the good characters presented by Toni attracts amazement and invites sympathy from the readers. Keywords: character, fortitude, self control, hard work.